Career profiles in the "new career": evidence of their prevalence and correlates. Issue 4 (8th August 2016) - Kuron, Lisa K.J.; Schweitzer, Linda; Lyons, Sean; Ng, Eddy S.W.
Abstract : Purpose: This study investigates the relationship between "new career" profiles (Briscoe and Hall, 2006) and two sets of career factors: agency (i.e. career commitment, self-efficacy, and work locus of control), and career attitudes (i.e. salience and satisfaction). Thus, the purpose of this paper is to understand whether career profiles are a valuable way to understand careers in the modern career era, and if so, which profiles exist, and what differences exist across the profiles. Design/methodology/approach: The participants in this study were 1, 987 managers and professionals, recruited from a large database of potential respondents. Cluster analysis determined which profiles were apparent among the participants through a two-step clustering procedure using the Bayesian information criterion algorithm. The authors then compared the clusters using analysis of variance (ANOVA) with cluster membership as the independent variable and the career agency and attitude variables and age as the dependent variables. Findings: Cluster analysis of the protean and boundaryless career attitudes of 1, 987 respondents identified three career profiles: Trapped/Lost, Protean Career Architects, and Solid Citizens. ANOVA confirmed that people indicative of the three profiles differed significantly on all study variables. The findings suggest that the three different career profiles predict important differences in career variables and outcomes that are relevant to individual progression and growth needs and may be a valuable way to study contemporary careers. In particular, the person-centred approach acknowledges that the protean and boundaryless career concepts are related though distinct concepts that can be combined to show that individuals vary in the degree to which their career orientations are consistent with contemporary career constructs. Research limitations/implications: The authors have demonstrated that career profiles are a meaningful way to categorize career actors on the basis of their career orientation, as well as their scores on a host of important career variables. Although the study benefits from a large sample and a valid measure of career profiles, it does have some limitations. First, the authors relied on self-reported data gathered on a single survey questionnaire. Furthermore, because the study is cross-sectional, the authors cannot examine the long-term impact of career profile on outcomes such as career satisfaction or if career profiles are enduring or malleable over time. Practical implications: From a practical perspective, it may be incumbent on organizations, career counsellors and individuals to develop an awareness to which career profile individuals belong (DeFillippi and Arthur, 1996). Doing so may offer insight into the likely challenges that career actors will face as their career unfolds, and ideally help individuals develop career management strategies to create career growth, rather than a more passive and reactive approach. A number of implications for each of the three career profiles are offered within the paper. Originality/value: Utilizing a two-step clustering procedure, the authors provide empirical evidence of three of the 16 career profiles proposed by Briscoe and Hall (2006): Trapped/Lost, Protean Career Architects and Solid Citizens. Next, the authors explored the utility of the profiles for career development and demonstrated significant differences in career-related psychological factor and attitudes across profiles. Finally, the authors take a person-centric approach to career orientation, allowing for individual differences in career enactment. Overall, the results of this study show that career profiles are a highly useful composite that reflect important patterns relative to new career variables.